Furosemide as a factor to deteriorate therapeutic efficacy of rifaximin in patients with decompensated cirrhosis. Issue 11 (26th September 2020) - Uchida, Yoshihito; Tsuji, Shohei; Uemura, Hayato; Kouyama, Jun‐ichi; Naiki, Kayoko; Sugawara, Kayoko; Nakao, Masamitsu; Inao, Mie; Nakayama, Nobuaki; Imai, Yukinori; Tomiya, Tomoaki; Mochida, Satoshi
Abstract : Aim: To optimize the therapeutic strategy for cirrhotic patients manifesting hepatic encephalopathy, factors affecting the outcome of patients receiving rifaximin were evaluated. Methods: The subjects were 95 patients receiving rifaximin. Serum ammonia levels were measured serially during rifaximin treatment. Factors associated with long‐term outcomes and cumulative survival rates were evaluated. Results: Serum ammonia levels were decreased at 4 weeks after rifaximin treatment compared to the levels at baseline even in patients receiving rifaximin as an add‐on therapy with lactitol hydrate ( P < 0.001) and reduction values were negatively correlated with the maximal diameter of portosystemic shunts (r = −0.275, P = 0.009). Overt encephalopathy occurred in 37 patients (38.9%) during rifaximin treatment, and the hazard function analysis identified 90 days as a high‐risk term for developing the first‐time overt encephalopathy. Thus, the long‐term outcome was judged as favorable in 77 patients (81.1%) in whom overt encephalopathy was absent for at least 90 days during rifaximin initiation. A multivariate analysis revealed that furosemide, especially at daily doses of ≥20 mg both at baseline and during rifaximin treatment, was a significant factor associated with unfavorable outcome ( P = 0.009 and P = 0.022, respectively) as well as occurrence and recurrence of overt encephalopathy ( P = 0.012). Moreover, furosemide treatment significantly deteriorated the cumulative survival rate of patients receiving rifaximin ( P = 0.026). Conclusion: Furosemide contributed to the deteriorated outcome of patients receiving rifaximin. Consequently, rifaximin should be given before increasing the furosemide dose, and the furosemide dose should not be increased during rifaximin treatment.